2022
DOI: 10.5937/bizinfo2202099m
|View full text |Cite
|
Sign up to set email alerts
|

Economic indicators of profitability in the production of organic and conventional food and psychological ways of overcoming the crisis in managers due to the possible decline of business during the COVID-19 pandemic

Abstract: The COVID-19 virus pandemic has led to huge changes in the business of many companies. Managers and owners of companies were most affected, so in one segment of this paper, certain psychological ways that are available to people when it comes to overcoming various crises. Considering that profitable business is a condition for the survival of companies, in this paper, a comparison of profitability in the production of organic and conventional food was performed. ROA and ROE were calculated on a sample of 150 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Rural tourism is becoming more and more relevant, as shown by another research results, according to which tourists from Serbia visit rural destinations once or twice a year, about 36%, while about 40% of tourists visit them at least three or more times per year (Tomić et al, 2020). In addition to untouched nature, the advantages of rural destinations are also traditional meals, which are often much healthier than conventional, due to their organic origin (Mitić and Čolović, 2023a;Mitić and Čolović, 2023b). Therefore, agritourism should be included as one of the main tourist offers, especially since it enables the development of rural areas and agriculture primarily and then the entire tourist offer of Serbia (Wojcieszak-Zbierska et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Rural tourism is becoming more and more relevant, as shown by another research results, according to which tourists from Serbia visit rural destinations once or twice a year, about 36%, while about 40% of tourists visit them at least three or more times per year (Tomić et al, 2020). In addition to untouched nature, the advantages of rural destinations are also traditional meals, which are often much healthier than conventional, due to their organic origin (Mitić and Čolović, 2023a;Mitić and Čolović, 2023b). Therefore, agritourism should be included as one of the main tourist offers, especially since it enables the development of rural areas and agriculture primarily and then the entire tourist offer of Serbia (Wojcieszak-Zbierska et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Also, companies engaged in the production of organic food record an increase in sales directly or online and an increase in the number of consumers who buy organic food during the COVID-19 pandemic (Mitić & Čolović, 2023a). Also, these companies report an increase in the level of profitability due to the effects of the COVID-19 pandemic (Mitić & Čolović, 2023b). A sample survey of the impact of COVID-19 on the solvency of 12,387 non-financial listed companies in 15 EU member states showed that manufacturing, mining and retail firms are vulnerable to liquidity problems due to falling market capitalization (Mirza et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the classic purchase of organic products due to the Covid-19 Pandemic, an increasing number of consumers decide to purchase these products online (Mitić and Čolović, 2023b). This leads to an increase in the value of this market and thus to a higher profit and liquidity for producers of organic food (Mitić and Čolović, 2023a;Mitić and Čolović, 2023c). With the increase in the profits of producers and sellers of organic food, their motivation to provide consumers with a wider range of available organic products, primarily organic foods, also increases.…”
Section: Introductionmentioning
confidence: 99%